Study of Emotional Intelligence and Study Habits of B.Ed. Trainees - Shivani Vijaykumar Suthar (Researchparks Publishing, 2023)
The main purpose of Educational is to develop values of physical, mental, intellectual spiritual social and emotional in human being. The importance of Emotional Intelligence is increased than intelligence at work, academic or social place. This is too much importance of emotions in human life B.Ed. trainees are crucial factor for social and national development. So, the researchers has decided to study on this topic. The objective of present study to know the Emotional Intelligence of B.Ed. trainees in relation to their study habits. Study habits play a major role in individuals achievement and success. The researcher has collected the data from 100 sample of B.Ed. trainees by Random sampling method and She applied statistical techniques such as mean, median, interpreted the data, she found that there was no significant difference between emotional intelligence of male and female B.Ed. trainees. The result is also shown that there was no significant difference between B.Ed. trainees with emotional intelligence having good and poor study habits. This research will so helped for students, administrators and as well as academic institutional.